2007
DOI: 10.1086/519268
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Epidemiologic Analysis of Acute Pyelonephritis

Abstract: Background. Acute pyelonephritis is a potentially severe disease for which there are few population-based studies. We performed a population-based analysis of trends in the incidence, microbial etiology, antimicrobial resistance, and antimicrobial therapy of outpatient and inpatient pyelonephritis.Methods. A total of 4887 enrollees of Group Health Cooperative, based in Seattle, Washington, who received an International Classification of Diseases, Ninth Revision, Clinical Modification, diagnosis of acute pyelon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
187
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(212 citation statements)
references
References 38 publications
15
187
1
9
Order By: Relevance
“…coli üriner sistem enfeksiyonu etkenlerinin %70-80'ini oluştururken, K. pneumoniae, Proteus mirabilis gibi diğer enterik çomaklar ve Staphylococcus saprophyticus diğer önde gelen etkenlerdir (21) . Ürosepsis olgularında E. coli en sık (%52) saptanan mikrobiyoloji etken olarak bildirilmiştir (22) .…”
Section: Discussionunclassified
“…coli üriner sistem enfeksiyonu etkenlerinin %70-80'ini oluştururken, K. pneumoniae, Proteus mirabilis gibi diğer enterik çomaklar ve Staphylococcus saprophyticus diğer önde gelen etkenlerdir (21) . Ürosepsis olgularında E. coli en sık (%52) saptanan mikrobiyoloji etken olarak bildirilmiştir (22) .…”
Section: Discussionunclassified
“…A European study showed that resistant microorganisms correlated highly with empirical antibiotics in patients with acute pyelonephritis (Efstathiou et al 2003). An American 5-year epidemiological study revealed that the standard regimen for acute pyelonephritis had been shifted due to increasing resistance of microorganisms (Czaja et al 2007). Infection by antibiotic-resistant microorganisms is an international problem, and there is a continuing need to discuss and improve the proper use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In regions with low levels of fluoroquinolone resistance, fluoroquinolones are the preferred antimicrobial agents for oral therapy [33].…”
Section: Fluoroquinolonementioning
confidence: 99%